Undocumented Immigration and Unemployment of U.S. Youth and Minority Workers: Econometric Evidence - Winegarden, C. R.; Khor, Lay Boon (The Review of Economics and Statistics, 1991)
The authors use Census-based data on the state distribution of the undocumented-alien population in analyzing the relationship between that population and unemployment among youth and minority workers. Regression results from their two-equation models do not support commonly expressed fears that undocumented immigration has caused any substantial increases in joblessness among these presumably vulnerable groups, although small amounts of displacement are indicated. A sizable reverse effect is evident: undocumented immigrants tend to concentrate in states where labor markets for these marginal groups are most favorable. Copyright 1991 by MIT Press.